The relationship between fat distribution in central region and comorbidities in obese people: Based on NHANES 2011–2018 - Liu, Chen-An; Liu, Tong; Ruan, Guo-Tian; Ge, Yi-Zhong; Song, Meng-Meng; Xie, Hai-Lun; Lin, Shi-Qi; Deng, Li; Zhang, He-Yang; Zhang, Qi; Shi, Han-Ping (Frontiers in Endocrinology, 2023)
Background: Central obesity is closely related to comorbidity, while the relationship between fat accumulation pattern and abnormal distribution in different parts of the central region of obese people and comorbidity is not clear. This study aimed to explore the relationship between fat distribution in central region and comorbidity among obese participants. Methods: We used observational data of NHANES 2011–2018 to identify 12 obesity-related comorbidities in 7 categories based on questionnaire responses from participants. Fat distribution is expressed by fat ratio, including Android, Gynoid, visceral, subcutaneous, visceral/subcutaneous (V/S), and total abdominal fat ratio. Logistic regression analysis were utilized to elucidate the association between fat distribution and comorbidity. Results: The comorbidity rate was about 54.1% among 4899 obese participants (weighted 60,180,984, 41.35 ±11.16 years, 57.5% female). There were differences in fat distribution across the sexes and ages. Among men, Android fat ratio (OR, 4.21, 95% CI, 1.54–11.50, Ptrend=0.007), visceral fat ratio (OR, 2.16, 95% CI, 1.42–3.29, Ptrend<0.001) and V/S (OR, 2.07, 95% CI, 1.43–2.99, Ptrend<0.001) were independent risk factors for comorbidity. Among these, there was a "J" shape correlation between Android fat ratio and comorbidity risk, while visceral fat ratio and V/S exhibited linear relationships with comorbidity risk. The Gynoid fat ratio (OR, 0.87, 95%CI, 0.80–0.95, Ptrend=0.001) and subcutaneous fat ratio (OR, 0.81, 95%CI, 0.67–0.98, Ptrend=0.016) both performed a protective role in the risk of comorbidity. In women, Android fat ratio (OR, 4.65, 95% CI, 2.11–10.24, Ptrend=0.020), visceral fat ratio (OR, 1.83, 95% CI, 1.31–2.56, Ptrend=0.001), and V/S (OR, 1.80, 95% CI, 1.32–2.45, Ptrend=0.020) were also independent risk factors for comorbidity, with a dose-response relationship similar to that of men. Only the Gynoid fat ratio (OR, 0.93, 95% CI, 0.87–0.99, Ptrend=0.016) had a protective effect on female comorbidity. This association was also seen in obese participants of different age groups, comorbidity numbers, and comorbidity types, although it was more statistically significant in older, complex comorbidity, cardiovascular, cerebrovascular, and metabolic diseases. Conclusions: In the obese population, there were strong correlation between fat distribution in central region and comorbidity, which was affected by sex, age, number of comorbidities, and type of comorbidity.